Every day students in schools Matter–reasons for not attending the School: evidence from advanced level Students - Shakira, M.N.F.; Kengatharan, N. (University of Jaffna, 2019)
The reasons for students’ absenteeism may vary across nations depending on country and cultural differences. Studies on students’ absenteeism that have been investigated in the West are reflective of such cultural contexts and therefore, the findings cannot be directly applied to another cultural context. There is a dearth of such studies in Asian and other similar developing countries. Consequently, the present study aims to discover factors determining students’ absenteeism in Sri Lanka. Strongly based on philosophical assumptions, the present study mainly employed a survey research strategy and data were primarily garnered from a self-administrated questionnaire. A total of 129 Advanced level students representing Arts and commerce streams were conveniently selected from five schools, namely KG/MW Baduriya Central College, KG/MW Zahira National School, KG/MW Mayurapada National School, KG/MW Nooraniya Muslim Vidhyalaya and KG/MW Mederigama Central College located Mawanella Zone in Sabaragamuwa province. The study revealed six factors determining students’ absenteeism, named student-preference, teacher and subject, physical and mental capabilities, non-collegiate, classroom facility and personal factors. Needless to say, the current study made several theoretical and practical implications.
Keywords: Students’ absenteeism; Student-preference; Physical and mental capabilities; Non-collegiate; Classroom facility; Teacher and subject